Peningkatan Keterampilan Berbahasa Indonesia Pemandu Wisata Thailand untuk Pelancong dari Indonesia - Raheni Suhita; Budhi Setiawan; Muhammad Rohmadi; Kundharu Saddhono; Aldi Dwi Saputra; Maulana Danar Maaliki H (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Indonesian tourists are one of the largest groups of travelers visiting Thailand. The high interest of Indonesian travelers in tourist destinations in Thailand is not supported by the number of tour guides skilled in the Indonesian language. The purpose of this international community service is to improve the competence of local tour guides in Thailand, particularly in terms of Indonesian language skills. The urgency of this service is to address the need for local Thai tour guides who are proficient in Indonesian. Skilled Indonesian-speaking local Thai tour guides are expected to provide optimal service to the increasing number of Indonesian tourists. The method of this service involves intensive assistance by Thammasat University students as tutors and translators. Thammasat students who are already proficient in Indonesian will provide Indonesian language training to local Thai tour guides. This assistance includes interactive learning sessions, conversation simulations, and direct practice in real tourist situations to enhance the communication skills of the tour guides. The results of the service show a significant improvement in the Indonesian language skills of 15 local Thai tour guides. This is evident from their ability to communicate more fluently and confidently with tourists from Indonesia. The group of local Thai tour guides also reported increased satisfaction in the services they provided, as well as positive feedback from Indonesian tourists. Based on these results, the assistance provided by the service team, supported by Thammasat University students, was effective in enhancing the language competence of local Thai tour guides. This service activity has a positive impact on the experience of Indonesian tourists and strengthens the bilateral tourism sector of both countries.